2018
DOI: 10.3390/rs10050701
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Canopy Height Profiles Extracted from Ku-band Profile Radar Waveforms and LiDAR Data

Abstract: An airborne Ku-band frequency-modulated continuous waveform (FM-CW) profiling radar, Tomoradar, records the backscatter signal from the canopy surface and the underlying ground in the southern boreal forest zone of Finland. The recorded waveforms are transformed into canopy height profiles (CHP) with a similar methodology utilized in large-footprint light detection and ranging (LiDAR). The point cloud data simultaneously collected by a Velodyne ® VLP-16 LiDAR on-board the same platform represent the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…For lidar, it is hard to detect the detailed information in complex canopy and understory vegetation, due to the mutual shielding of branches and leaves. Zhou et al compared the canopy height profiles extracted from the Tomoradar waveforms and lidar data; both data were used in this paper [14]. They found that the locations of the canopy height profiles acquired from the lidar were obviously higher than those from the Tomoradar.…”
Section: Comparisons Of Accuracies In Waveform Simulationmentioning
confidence: 96%
“…For lidar, it is hard to detect the detailed information in complex canopy and understory vegetation, due to the mutual shielding of branches and leaves. Zhou et al compared the canopy height profiles extracted from the Tomoradar waveforms and lidar data; both data were used in this paper [14]. They found that the locations of the canopy height profiles acquired from the lidar were obviously higher than those from the Tomoradar.…”
Section: Comparisons Of Accuracies In Waveform Simulationmentioning
confidence: 96%
“…We compared each Tomoradar average waveform with the simulated profile radar waveforms using the waveform matching method [39]. The ground points of both Tomoradar waveforms and simulated waveforms were identified firstly [28] and the range from the ground point to 2 m above the ground point was treated as ground scattering contribution [21]. In order to correspond to the difference in ground scattering intensity caused by possible ground features (such as different ground cover, moisture, or micro-topography) in the actual scenes, we performed differential amplification on the ground scattering contribution of the simulated waveform, that is, the ground contribution was multiplied by four coefficients of 0.1, 0.4, 0.7, and 1.3.…”
Section: Waveform Matching and Canopy Lai Estimationmentioning
confidence: 99%
“…The Tomoradar and lidar measurements were time-tagged with GPS time and coincided in a centimeter-level manner. The suites of all instruments on the helicopter are presented in Figure 1b [10]. The field test was carried in the autumn of 2016 under partly cloudy conditions.…”
Section: Study Areamentioning
confidence: 99%
“…Tomoradar can provide four linear polarization measuring capabilities in Ku band based bistatic configuration with 15 cm range solution, to improve the understanding of the radar backscatter response for forestry mapping and inventories. Subsequent studies on forest inventory, especially for vertical forest structure using FMCW radar data have been conducted in the past few years [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%